The Moral Argument of Theism - Barrow, George A. (Harvard theological review, 1911)
Construction rather than destruction is, in its time and place, a good motto, but to attempt a reconstruction without first clearing the ground is likely to make the resulting building unstable. In the last quarter-century we have been attacking one by one the received views in theology, and now we are ready for constructive work, but unfortunately, as many students know who are in theological seminaries, even some marked as “liberal,” there is little fundamental criticism of the general basis of theism. Theology has made use of the philosophical progress, but has made comparatively little advance in its own field. So we find the traditional arguments for God's existence repeated in only very slightly modified form. It is in the attempt to bring home to us the necessity for a thorough-going criticism that this examination of one of the traditional arguments for God's existence has been undertaken.